PERAN PREFERENSI MEREK DALAM MEMEDIASI HUBUNGAN ANTARA EKUITAS MEREK DENGAN NIAT BELI - Adnyana, Made; Respati, Ni Nyoman Rsi (E-Jurnal Manajemen, 2019)
This study aims to explain the effect of brand equity on brand preference, the influence of brand equity on buying intentions, the influence of brand preferences on buying intentions, and the role of brand preferences in mediating the relationship between brand equity and purchase intentions. This study was conducted in the city of Denpasar with 110 respondents.Data collection method used is simple random sampling method with SEM analysis technique. The results showed that brand equity has a positive and significant effect on brand preference. Brand equity has a positive and significant impact on purchasing intentions. Brand preference has a positive and significant impact on purchasing intentions. Brand preference as a mediating variable significantly indirectly influences purchase intentions through brand equity variables.Garuda Indonesia needs to pay attention to brand loyalty because brand loyalty is the only element of brand equity associated with future earnings gain. Garuda Indonesia should further enhance the company's brand preference in the minds of potential customers for the creation of purchase intentions.   Keywords: brand equity, brand preference, purchase intention